2021
DOI: 10.1088/1361-6463/ac0b11
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface modification of defective KTaO3 by ionizing ion irradiation

Abstract: The synergistic effect of nuclear (S n) and electronic (S e) energy loss observed in some ABO3 perovskites has attracted considerable attention due to the real possibility to modify various near-surface properties, such as the electronic and optical properties, by patterning ion tracks in the defective near-surface regions. In this study, we show that low-energy ion-induced disordering in conjunction with ionizing ion irradiation (18 MeV Si, 21 MeV Ni and 91.6 MeV Xe) is a promising approach for tailoring ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…In very good accordance with previous experimental studies, irradiation at 300 K with 2.0 MeV Au ions to an ion fluence of 0.11 ions nm −2 has resulted in the creation of a predamaged layer with a maximum initial fractional disorder state (f 0 ) of ∼0.35 on the Ta sublattice. According to previous damage accumulation curves [12], the sample with f 0 ∼ 0.35 corresponds to the intermediate level of disorder, where interstitial point defects, interstitial clusters and some minor nanoscale amorphous domains are expected to be present within the layer irradiated with 2.0 MeV Au ions to an ion fluence of 0.11 ions nm −2 [16]. The occurrence of a competitive two-stage phase transition process in pre-damaged KTaO 3 12 MeV O ions at the indicated ion fluences.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In very good accordance with previous experimental studies, irradiation at 300 K with 2.0 MeV Au ions to an ion fluence of 0.11 ions nm −2 has resulted in the creation of a predamaged layer with a maximum initial fractional disorder state (f 0 ) of ∼0.35 on the Ta sublattice. According to previous damage accumulation curves [12], the sample with f 0 ∼ 0.35 corresponds to the intermediate level of disorder, where interstitial point defects, interstitial clusters and some minor nanoscale amorphous domains are expected to be present within the layer irradiated with 2.0 MeV Au ions to an ion fluence of 0.11 ions nm −2 [16]. The occurrence of a competitive two-stage phase transition process in pre-damaged KTaO 3 12 MeV O ions at the indicated ion fluences.…”
Section: Resultsmentioning
confidence: 87%
“…In crystalline KTaO 3 , ion irradiation with low-energy ion results in amorphization of the implanted layer at a given ion fluence (or dose), through a defect-stimulated mechanism [12], and the corresponding critical ion fluence necessary for amorphization shifts to higher values with increasing irradiation temperature [13,14]. The response of pristine crystalline KTaO 3 to high-energy ion irradiations has also been the subject of several investigations [8,15,16], and these lead to the conclusion that pristine KTaO 3 is relatively sensitive to swift heavy ions irradiations (E > 1 MeV amu −1 ) and undergoes discontinuous to continuous amorphous ion track formation with increasing ion energy or electronic energy loss. Discontinuous amorphous track formation in KTaO 3 occurs for S e > 11 keV nm −1 [15,16], while continuous ion tracks are observed at much higher S e values (S e > 23 keV nm −1 ) [8,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bae et al reported the preparation of single terminated KTO substrates using buffered hydrofluoric acid (BHF) followed by high temperature annealing. [139,174,175] B-site terminated surfaces were achieved by controlling the concentration of BHF, and the temperature and time of annealing. The major drawback of this technique is the use of the strong etchant which may leave a rough surface that would affect the film growth.…”
Section: Treatment Of the Substrate Surfacementioning
confidence: 99%